Novel hard and unusual superconducting monoclinic phase of FeB2C2: An ab initio evolutionary study - Komsilp Kotmool; Udomsilp Pinsook; Wei Luo; Rajeev Ahuja; Thiti Bovornratanaraks (Journal of Applied Physics, 2024)
This study focuses on conducting an ab initio evolutionary investigation to search for stable polymorphs of iron diborocarbides with the formula FeB2C2. We also examined other forms of C contents, including FeB3C and FeBC3. Our findings reveal that the lowest energetic structure of FeB2C2 is a semimetallic monoclinic phase with a space group (s.g.) of C2/m and a metastable metallic phase of FeB2C2 is an orthorhombic structure with s.g. of Pmmm. In addition, structural and relative properties of FeB3C and FeBC3 are performed and discussed to compare with FeB2C2. All predicted structures are dynamically and elastically stable, verified without negative phonon frequency and Born criteria, respectively. We also analyzed the energetic stability through calculated cohesive and formation energies, which showed that C2/m-FeB2C2 is stable at low pressure. Interestingly, the C2/m and Pmmm phases of FeB2C2 are hard materials with Vickers hardness (Hv) of 22.40 and 27.52 GPa, respectively. Additionally, we examined the electron–phonon coupling of both FeB2C2 phases. Unexpectedly, we found that the semimetallic C2/m-FeB2C2 phase is a superconductor with a significant superconducting temperature (Tc) exceeding 6 K. These findings provide some novel results for the Fe–B–C system and pave the way for investigating other metal borocarbides and related ternary compounds.
Keywords: Boron and Carbon Nanomaterials Research; Metal and Thin Film Mechanics; Advanced materials and composites